"The Market That Just Grew Up": How Eaton's Fashioned the Teenaged Consumer in Mid-twentieth-century Canada - Rollwagen, Katharine E (Université d'Ottawa / University of Ottawa, 2012)
This thesis focuses on the emergence of the teenaged consumer as a market segment in Canada during the 1930s, 1940s, and 1950s. It challenges the notion that teenagers were of little interest to retailers until economics and demographics shaped the more numerous and prosperous post-war teenagers of the Baby Boom generation. Using evidence from corporate records and analysis of mail order catalogues, the study examines how department store retailer, the T. Eaton Company, Limited, began to cultivate a distinct and lucrative teenaged consumer in the 1930s, and thereby began shaping the teenaged consumer. The thesis contextualizes the case study of Eaton’s by exploring the varied expectations that adults had of young people at the time, using census records and magazines (Chatelaine, Canadian Home Journal and Mayfair) to explore concerns about young people’s transition to adulthood. It then focuses on how Eaton’s made a concerted and sustained effort to attract teenager customers to its catalogue and stores. Analysis of its semi-annual catalogue highlights the emergence of specialized clothing size ranges and styles, revealing that Eaton’s increasingly viewed the teenaged years as an important in-between life stage. Eaton’s also instituted teenage advisory councils to both glean market trends and provide a venue for what it considered education for novice consumers. Eaton’s presented consumption as a way to prepare young people for adult roles, legitimizing teenaged participation in the consumer marketplace and contributing to wider debates about when and how teenaged Canadians should reach maturity.
Keywords: Canada; twentieth century; teenagers; childhood; growing up; students; Eaton's; department store; advertising; advisory councils; clothing; speciality sizes; retail; mail order catalogues; consumer magazines; Chatelaine; Mayfair; Canadian Home Journal; gender; Canadian census